Prevalence and risk factors of cognitive impairment in Chinese patients with hypertension: a systematic review and meta-analysis - Xie, Cheng; Zhong, Dongling; Zhang, Yue; Liu, Xiaobo; Zhang, Lili; Luo, Xiao; Gong, Yimeng; Jiang, Wei; Jin, Rongjiang; Li, Juan (Frontiers in Neurology, 2024)
Background Cognitive impairment is prevalent in Chinese patients with hypertension; however, current evidence on prevalence and risk factors is required to be synthesized. Objectives This systematic review and meta-analysis aimed to evaluate the prevalence and risk factors of cognitive impairment in Chinese patients with hypertension. Methods Two reviewers independently searched PubMed, Web of Science, Embase, The Cochrane Library, CNKI, CBM, the Wanfang database, and the VIP database from their inception to 7 June 2023. The gray literature and the reference lists of the included studies were also retrieved manually. Moreover, we also independently performed the eligibility screening, data extraction, and data synthesis. The primary outcome was the prevalence of cognitive impairment in Chinese patients with hypertension, and the secondary outcomes were the risk factors for cognitive impairment in patients with hypertension. R (version 4.0.3) was used for data synthesis. Results In total, 82 studies involving 53,623 patients with hypertension were included in this meta-analysis. The pooled prevalence of cognitive impairment in patients with hypertension was 37.6% (95% CI: 33.2–42.2%). A total of 12 risk factors, including advanced age (r = −0.34, 95% CI: −0.45, −0.21), female sex (OR = 1.15, 95% CI: 1.01–1.32), BMI > 24 Kg/m2 (OR = 1.76, 95% CI: 1.04–3.00), lower educational level (OR = 2.01, 95% CI: 1.10–3.67), single status (OR = 1.63, 95% CI: 1.32–2.02), complications with diabetes (OR = 1.44, 95% CI: 1.14–1.80), coronary heart disease (OR = 1.49, 95% CI: 1.12–1.97), higher stage of hypertension [stage 3 vs. stage 1, OR = 3.08, 95% CI: 1.82–5.22; stage 2 vs. stage 1, OR = 1.83, 95% CI: 1.29–2.60], no regular physical activity (OR = 0.40, 95% CI: 0.21–0.77), higher levels of systolic blood pressure (r = −0.25, 95% CI: −0.42, −0.08), Hcy (r = −0.39, 95% CI: −0.63, −0.09), and IL-6 (r = −0.26, 95% CI: −0.48, −0.02) were detected. Conclusion Cognitive impairment is prevalent in Chinese patients with hypertension, and the increased prevalence was associated with several demographic characteristics, complicated disease, no regular physical activity, worse hypertension status (higher stages and SBP), and high levels of biomarkers. Therefore, more attention should be paid to the early identification and treatment of patients with hypertension who are at high risk for cognitive impairment in clinical practice. In addition, relevant risk factors should be controlled to reduce the incidence of cognitive impairment. Systematic review registration http://www.crd.york.ac.uk/PROSPERO, identifier [CRD42023410437].